B10 Cells Are Associated With Clinical Prognosis During Adult Symptomatic Acute HBV Infection - Liu, Yali; Du, Xiaofei; Lu, Junfeng; Ma, Lina; Jing, Yi; Ben, Haijing; Chen, Xinyue; Zhang, Jing (Frontiers in Immunology, 2022)
There are few reports about the role of B10 cells in acute hepatitis B (AHB) infection. In this study, based on 48 acute hepatitis B infected patients, we analysis the correlation of B10 cells with HBV clinical prognosis. The results showed that B10 was positively correlated with HBsAg and HBeAg and inversely correlated with anti-HBs. The level of B10 in one week before HBsAg clearance was significantly lower than 2 weeks prior to HBsAg clearance and after 1-2 weeks of HBsAg clearance. B10 cell frequency displayed no correlation with HBV DNA; however, it showed significant temporal synchronization with hepatic inflammatory markers such as ALT. B10 level also associated with hospitalization time. These results indicated that B10 is closely related to the clinical prognosis of acute HBV infection.